Characterization of MoSe2 thin film deposited at room temperature from solution phase - Hankare, P. P.; Patil, A. A.; Chate, P. A.; Garadkar, K. M.; Sathe, D. J.; Manikshete, A. H.; Mulla, Imtiaz S. (Journal of Crystal Growth, 2008)
A simple, low-temperature method has been developed to synthesis molybdenum diselenide semiconductor thin films, based on the chemical reaction of conlplexed ammonium molybdate, hydrazine hydrate and sodium Selenosulphate in aqueous alkaline medium. The deposition parameter of the MoSe2 thin film is interpreted in the present investigation. The films were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), optical absorption and electrical measurements. The deposited film was found to be polycrystalline in hexagonal form. The direct band gap `E-g' for the film was found to be 1.43eV and electrical conductivity in the order of 10(-2)(Omega cm)(-1) with n-type conduction mechanism. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Crystal morphology; Growth from solution; Inorganic compound; Polycrystalline deposition; Semiconducting materials; X-ray diffraction

Structural and surface morphological properties of chemically deposited Mo0.5W0.5S2 thin film - Patil, A. A.; Hankare, P. P.; Gaikwad, A. B.; Garadkar, K. M. (Journal of Materials Science-Materials in Electronics, 2012)
Preparation of layered type semiconductor Mo0.5W0.5S2- thin films has been successfully done by using chemical bath deposition method. Objective of the studies are related to structural, optical, morphological and electrical properties of the thin films. The preparation method is based on the reaction between tartarate complex of Mo and W with thiourea in an aqueous alkaline medium at 363 K. X-Ray diffraction reveals a polycrystalline film composed of both MoS2 and WS2 phases. The optical study shows that the band gap of the film is 1.6 eV. Electrical conductivity is high which is in the order of 10(-3)-10(-2) (Omega cm)(-1).